Agriculture in Eighth Plan A Background Note Socio-Economic Group Meeting June 14, 1990 - Planning Commission (Planning Commission Government of India, 1990)
The Eighth Plan Agriculture Document outlines India’s strategic approach to enhancing agricultural productivity and rural livelihoods. Agriculture remains central to India’s economy, employing nearly 75% of the population, yet growth has been uneven, favoring Green Revolution states. Key challenges include nutritional deficits, regional disparities, inadequate irrigation, and limited support for small-scale farmers. The Plan emphasizes increasing crop productivity, promoting agro-based industries, sustainable natural resource management, and fostering participatory planning at the grassroots level. Strategic directions include agro-climatic zoning, watershed development, rainfed agriculture technologies, and targeted interventions for underperforming eastern states. Strengthening input delivery systems, agricultural research, and extension services is prioritized to ensure technology adoption, particularly by women and rural communities. Complementary measures involve robust price policies, export promotion, and improvements in marketing and rural infrastructure. Overall, the Eighth Plan aims for holistic agricultural development, balancing productivity, employment, and food security while addressing socio-economic and regional inequities.
Agriculture Division Planning Commission Government of India New Delhi - 110o01
Keywords: Agriculture; Food Security; Rural Development; Green Revolution; Crop Productivity; Nutritional Deficit; Agro-Climatic Zones; Rainfed Agriculture; Agricultural Research; Irrigation; Price Policy; Extension Services